WOMEN'S AGENCY AND THE STATE IN CONTEMPORARY BRUNEI ([S.l.])
1 online resource
Keywords: This pioneering book presents a comprehensive overview of the role of women in Brunei's economy, society and public domain, from the historical and contemporary perspective.Making an important contribution to the study of women in Asia by focusing on Brunei, a country with many distinctive features, including governance by an Islamic sultan, guidance by a national philosophy of 'Malay Islamic Monarchy', and a unique intermingling of Malay and Chinese traditions and practices. Featuring contributions by Brunei women academics based in local tertiary institutions, it portrays the lives of women's in Brunei from their own perspective. It covers women's agency through several lenses, including the growing digital activism on issues of sexual harassment, women's empowerment, women entrepreneurship, agency in Chinese Bruneians' contemporary literary narratives and the recent role of women in Islamic development in Brunei. Some of the challenges and concerns raised by the authors might have policy implications.Bringing detailed and insightful scholarship on issues and themes of local concerns with a Brunei perspective, this book will appeal to students and scholars of Women's studies, Asian studies, Southeast Asian studies, and Islamic Studies.